2009
DOI: 10.1039/b802270d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water on elementary reaction steps in electrocatalysis

Abstract: We studied simple reaction pathways of molecules interacting with Pt(111) in the presence of water and ions using density functional theory within the generalized gradient approximation. We particularly focus on the dissociation of H2 and O2 on Pt(111) which represent important reaction steps in the hydrogen evolution/ oxidation reaction and the oxygen reduction reaction, respectively. Because of the weak interaction of water with Pt(111), the electronic structure of the Pt electrode is hardly perturbed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 50 publications
6
69
3
Order By: Relevance
“…4B, it is not a direct consequence of changes in OH ads adsorption dynamics but rather it is related with changes in the EDL structure, due to changes in water dipole orientations. In this sense, theoretical results have shown that because of the weak interaction of water with Pt(111), the electronic structure of the Pt electrode is hardly perturbed by the presence of water and so, processes that occur directly at the electrode surface, such as specific adsorption or the dissociation from a chemisorbed molecular state, are only weakly influenced by water, while processes that occur further away from the electrode can be modified by the water environment through direct molecule-water interactions [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B, it is not a direct consequence of changes in OH ads adsorption dynamics but rather it is related with changes in the EDL structure, due to changes in water dipole orientations. In this sense, theoretical results have shown that because of the weak interaction of water with Pt(111), the electronic structure of the Pt electrode is hardly perturbed by the presence of water and so, processes that occur directly at the electrode surface, such as specific adsorption or the dissociation from a chemisorbed molecular state, are only weakly influenced by water, while processes that occur further away from the electrode can be modified by the water environment through direct molecule-water interactions [4].…”
Section: Resultsmentioning
confidence: 99%
“…2016, 262: 95-99. doi:10.1016/j.cattod.2015.08.046 structure in the interface and the electronic distribution in the metal, which may modify the electronic properties of the substrate [4][5][6][7][8]. However, while several studies on different Ptbased materials have shown that the ORR kinetics and mechanism are strongly affected by the nature and structure of electrodes [1,2,[9][10][11][12], the influence of interfacial water structure on the reaction is still poorly understood [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This will be particularly important if non-covalent interaction with other water molecules close to the surface can take place [47][48][49], especially if the applied potential is close enough to the formal potential of this species.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical studies provide an alternative tool to elucidate the phenomenon [13][14][15][16]. The Pt surface behavior has been studied under the presence of oxygen, water, oxygen/water, some chlorinated ions and carbon dioxide, using different computational methods like density functional theory (DFT), classical and ab initio molecular dynamics (MD) [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%